Effects of Processing on Electric Response of Carbon Black Filled Poly(methyl methacrylate)Composites against Organic Solvent Vapors - Dong, X.M.; FU, R.W.; ZHANG, M.Q.; Qin, Z.P.; Zhang, B.; Rong, M.Z.
Carbon black filled poly(methyl methacrylate)(CB/PMMA)composites were fabricated by solution mixing and polymerization filling, respectively. The effects of processing conditions on electrical conductivity of the composites and their electric responsivity against organic solvent vapors were investigated. The experimental results showed that molecular weight of the polymer matrix, carbon black content, and the composite film thickness greatly influence the response behaviors of the composites in solvent vapors. Furthermore, the composites prepared by polymerization filling have higher gas sensitivity, response rate, recovery rate, and reproducibility as compared to the composites by solution mixing. The sensing performance of the composites is found to be closely related to the microstructure of the materials, which provides possibilities for further improve the overall properties of the composites by altering the processing parameters.
Keywords: CARBON BLACK; POLY(METHYL METHACRYLATE); CONDUCTIVE POLYMER COMPOSITES; GAS SENSOR; PROCESSING